The Contribution of the Inquiry Learning Model to Student Scientific Argumentation Skills on Fluid - Tutut Nurita; An Nuril Maulida Fauziah; Muhamad Arif Mahdiannur; Enny Susiyawati (Jurnal Penelitian Pendidikan IPA, 2023)
The inquiry learning model is a model that facilitates the construction of students' scientific knowledge which can also improve students' argumentation skills. According to several research results, inquiry-based learning has proven to be effective in improving scientific argumentation skills because in the learning process students are directed in investigative activities to find scientific evidence as a basis for scientific argumentation. By considering the student learning process, the aim of this research is to describe whether the use of three types of inquiry learning models can teach fluid material and influence the student learning process, one of which is students' argumentation abilities. This research method uses mixed method triangulation. The instruments used were interview questionnaires and argumentation tests. The data obtained was then analyzed using simple statistical tests and N-gain scores. Interview data was analyzed to find out clarification of students' answers. The research results of the inquiry learning model were successful in developing argumentation skills, namely the n-gain score resulted in the use of the structured inquiry learning model gaining 0.88, the guided inquiry learning model 0.84 and the open inquiry learning model 0.74.